INTEGRASI GAME-BASED LEARNING BERBASIS GENIALLY UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI: TINJAUAN PUSTAKA - Aprilia Wulandari; M Hidayat; Erlida Amnie (JURNAL FIRNAS, 2026)
This study aims to analyze the effectiveness of Game-Based Learning (GBL) using the Genially platform in enhancing students' collaboration skills in physics learning. The research employed a literature review method by examining 23 relevant articles published in national and international journals. The findings indicate that the use of digital educational games, particularly Genially, has a positive impact on students' learning outcomes, motivation, and collaboration skills. Interactive features such as animations, quizzes, and simulations encourage active student participation through communication, teamwork, and collaborative problem-solving activities. Furthermore, Genially supports the development of 21st-century skills by promoting social responsibility, cooperation, and teamwork. Therefore, the integration of Game-Based Learning through the Genially platform is not only effective in improving students' cognitive achievement but also plays a significant role in developing collaborative skills essential for modern education.